The Influence of Social Support and Organizational Commitment on the Work Productivity of Preparation Department Employees at PT Adis Dimension Footwear, Tangerang Regency - Marbun, Larasti Gabriella; Fahmi, Khaerul (UJoST- Universal Journal of Science and Technology, 2026)
The purpose of this study was to determine how much influence social support and organizational commitment have on the work productivity of employees in the Preparation section at PT. Adis Dimension Footwear, Tangerang Regency.This study uses a quantitative descriptive method. The population in this study were all employees in the Preparation section at PT Adis Dimension Footwear, Tangerang Regency, totaling 351. The research sample consisted of 78 respondents. This study used the Slovin formula as a sample technique, so the sample in this study was 78 employees.The results of this study indicate that (1) partially, social support significantly influences the work productivity of employees in the Preparation section at PT. Adis Dimension Footwear, Tangerang Regency, as indicated by the calculated t value > t table (5.355 > 1.992) and a significance value of 0.000 which is smaller than the significance value of 0.05. Thus, Ha is accepted and H0 is rejected. (2) Partially, organizational commitment significantly influences the work productivity of employees in the Preparation section at PT. Adis Dimension Footwear, Tangerang Regency, as indicated by the calculated t value > t table (3.771 > 1.992) and a significance value of 0.000 which is smaller than the significance value of 0.05. Thus, Ha is accepted and H0 is rejected. (3) Simultaneously, social support and organizational commitment significantly influence the work productivity of employees in the Preparation section at PT. Adis Dimension Footwear Tangerang Regency, which is indicated by Fcount> Ftable (55.292> 3.12) with a significance level of 0.000, thus Ha is accepted and H0 is rejected.Based on the results of the study, it can be concluded that the variables of social support and organizational commitment, either partially or simultaneously, have a significant influence on the work productivity of employees in the Preparation section at PT. Adis Dimension Footwear Tangerang Regency.